Dental avulsion due to direct laryngoscopy during the induction of general anaesthesia and avulsed teeth in nasopharynx - Ozer, Ayse Belin; Erhan, Omer L.; Demirel, Ismail; Keles, Erol (BMJ Publishing Group, 2012)
General anaesthesia was induced to a 32-year-old female patient. During direct laryngoscopy, the four upper front incisors were avulsed and fell into the patient 's oral cavity without fracture. After endotracheal intubation, her oral cavity was searched laryngoscopically but the teeth were not found. Radiological findings of her chest and abdomen obtained by the C-armed x-ray device and endoscopic findings of the oesophagus were normal. Her head and neck imaging revealed a radiopaque lesion in the nasopharyngeal area. Later, the nasopharyngeal area was examined endoscopically and the teeth were removed following adenoidectomy. We emphasise that preoperative evaluation is essential for dental injuries, and patients with a risk of dental injury must be detected before surgery. The localisation of the broken teeth must be identified and removed, and one must keep in mind that the dental fragments can travel to the nasopharynx. Copyright 2012 BMJ Publishing Group. All rights reserved.
Keywords: famotidine; fentanyl; oxygen; prednisolone; thiopental; vecuronium; adenoidectomy; adult; anesthesia induction; article; bleeding; case report; edema; endotracheal intubation; extubation; female; foreign body; general anesthesia; human; hysteroscopy; incisor; laparoscopy; laryngoscope; laryngoscopy; nasopharynx; priority journal; tooth injury; X ray